Endothelial angiopoietin-2 overexpression in explanted livers identifies subjects at higher risk of recurrence of hepatocellular carcinoma after liver transplantation - Lasagni, Simone; Leonardi, Filippo; Pivetti, Alessandra; Di Marco, Lorenza; Ravaioli, Federico; Serenari, Matteo; Gitto, Stefano; Critelli, Rosina Maria; Milosa, Fabiola; Romanzi, Adriana; Mancarella, Serena; Dituri, Francesco; et al. (Frontiers in Oncology, 2022)
Background: Though the precise criteria for accessing LT are consistently being applied,HCC recurrence (HCC-R_LT) still affects more than 15% of the patients. We analysed the clinical, histopathological and biological features of patients with HCC to identify the predictive factors associated with cancer recurrence and survival after LT. Methods: We retrospectively analysed 441 patients with HCC who underwent LT in our Center. Overall,70 (15.8%) of them developed HCC-R_LT. We matched them by age at transplant and aetiology with 70 non-recurrent patients. A comparable cohort from the Liver Transplant Centre of Bologna served as validation. The clinical and biochemical characteristics and pre-LT criteria (Milan, Metroticket,Metroticket_AFP and AFP model) were evaluated. The histological analysis and immunohistochemistry for Angiopoietin-2 in the tumour and non-tumour tissue of explanted livers were performed. Patients’ follow-up was until death, last clinical evaluation or December 31st 2021. In patients with HCC-R_LT, the date of diagnosis of recurrence and anatomical site has been reported; if a biopsy of recurrence was available, histologic and immunohistochemical analyses were also performed. Results: Patients were followed up for a mean period of 62.7±54.7 months (median 39 months). A higher risk of HCC-R_LT was evident for factors related indirectly (AFP) or directly (endothelial Angiopoietin-2,microvascular invasion) with biological HCC aggressiveness. In multivariate analysis, only Angiopoietin-2 expression was independently associated with recurrence. Extremely high levels of endothelial Angiopoietin-2 expression were also found in hepatic recurrence and all different metastatic locations. At univariate analysis MELD, Metroticket_AFP Score, Edmondson-Steiner grade,microvascular invasion and endothelial Angiopoietin-2 were significant related with survival. At multivariate analysis, Angiopoietin-2 expression, Metroticket_AFP score, and MELD (both in training and validation cohorts) independently predicted mortality. At time-dependent Area Under Receiver operating characteristic curve analysis, the Endothelial Angiopoietin-2 expression had the highest specificity and sensitivity for recurrence (AUC 0.922, %CI 0.876-0.962, p<0.0001). Conclusions: Endothelial Angiopoietin-2 expression is a powerful independent predictor of post-LT tumour recurrence and mortality, highlighting the fundamental role of tumour biology in defining the patients’ prognosis after liver transplantation. The great advantage of endothelial Angiopoietin-2 is that it is evaluable in HCC biopsy before LT and could drive a patient’s priority on the waiting list.